Factors influencing non-use of drugs among male Filipino out-of-school youth - Buhain, Carmelo Jose A.
The study sought to identify factors influencing the non-use of drugs among Filipino out-of-school youth in both the micro- and macro-level environments in terms of personal vulnerability, family structure, peer selection and influence, social activity and social awareness. This study also explores the role of formal, informal and non-formal education in developing resilience to drugs. Study participants were five Filipino male out-of-school youth non-users ages 15-30 years old from Barangay Nangka in Marikina City. Data from questionnaire, life-story essay, unfinished statements, participant observation and social media post were triangulated and the modified grounded theory approach was utilized. The study reveals five factors influencing non use of drugs among Filipino male out-of-school youth: strong spiritual foundation, close family ties, positive peer relationship, interest in recreational activities and active community involvement. The contribution of formal, informal and non-formal education to the non-use of drugs among male Filipino OSY was found to be strongly relevant as it helps them in developing life skills and values base for a sound drug literacy. This study can serve as a basis in exploring other issues concerning drug use in the Philippines particularly those that can help provide evidence on the effectiveness of local drug prevention initiatives, as well as in strengthening the Values Education program in both formal and non-formal education.